Pengembangan Media Pembelajaran Multimedia Interaktif Materi Keragaman Suku Bangsa dan Agama di Indonesia pada Siswa Kelas IV Sekolah Dasar - Erika Dwi Yunita; Puri Selfi Cholifah; Imam Nawawi; Erika Dwi Yunita; Puri Selfi Cholifah (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2021)
Abstract: Learning media is a tool as an intermediary in the process of teaching and learning activities. Learning media in accordance with the development of technology and conditions at the time of covid can use media in digital form, one example is interactive multimedia. Based on the results of observations made at MI Islamiyah Tempursari, Lumajang district, it was found that teachers have not fully used learning media to support online learning activities carried out. This study has a goal, namely, to produce learning media products in the form of interactive multimedia on the material of ethnic and religious diversity in Indonesia class IV that is valid based on the validation of media experts, material experts, and practicality based on the results of user trials (teachers and students). This study uses the research and development (R and D) method developed by Dick and Carey. The model used in this research and development is the Borg and Gall model. Namely 10 stages that have been modified into 7 stages. Potentials and problems, data collection, product design, design validation, product revision, and trial use of product revisions. The trial design is a description of the activities carried out by researchers to determine the validity, attractiveness, and practicality of the developed media. The test subjects in the research and development of this learning media are media experts, material experts and product users, namely teachers and fourth grade students of MI Islamiyah Tempursari, Lumajang Regency. This research and development use the type of research data analysis techniques in the form of qualitative and quantitative descriptive analysis The results of the development of interactive multimedia include material on the diversity of ethnicities and religions in Indonesia on Theme 7 The beauty of diversity in my country for the fourth grade of elementary school. The developed interactive multimedia obtained a percentage of assessment by media experts, namely 100 percent or categorized as very valid media, the percentage of assessment by material experts with an average of 89 percent or categorized as very valid media. While the practicality of the developed media obtained a percentage of assessment by teachers of 96 percent or categorized as very practical media and the percentage of assessments carried out by students amounted to eighteen students, namely 99.62 percent or categorized as very practical media. The developed interactive multimedia learning media is categorized as a very valid and very practical media, and interactive multimedia learning media can be implemented in the next learning process. Further researchers can develop media with a wider scope. Abstrak: Media pembelajaran merupakan alat bantu sebagai perantara dalam proses kegiatan belajar mengajar. Media pembelajaran sesuai dengan berkembangnya teknologi dan kondisi pada saat covid dapat menggunakan media dalam bentuk digital, salah satu contoh yaitu multimedia interaktif. Berdasarkan hasil observasi yang dilakukan di MI Islamiyah Tempursari kabupaten Lumajang, ditemukan bahwa guru belum sepenuhnya menggunakan media pembelajaran untuk menunjang kegiatan pembelajaran online yang dilakukan. Penelitian ini memiliki tujuan yaitu, menghasilkan produk media pembelajaran berupa multimedia interaktif pada materi keragaman suku bangsa dan agama di Indonesia kelas IV yang valid berdasarkan validasi ahli media, ahli materi, serta kepraktisan berdasarkan hasil uji coba pengguna (guru dan siswa). Penelitian ini menggunakan metode research and development (R&D) yang dikembangkan oleh Dick dan Carey. Model yang digunakan pada penelitian dan pengembangan ini adalah model Borg and Gall. Yaitu 10 tahapan yang telah dimodifikasi menjadi 7 tahapan. Potensi dan masalah, pengumpulan data, desain produk, validasi desain, revisi produk, dan uji coba pemakaian revisi produk. Desain uji coba merupakan suatu gambaran kegiatan yang dilakukan peneliti untuk mengetahui kevalidan, kemenarikan, serta kepraktisan media yang dikembangkan. Subjek uji coba dalam penelitian dan pengembangan media pembelajaran ini yaitu ahli media, ahli materi dan pengguna produk yakni guru dan siswa kelas IV MI Islamiyah Tempursari Kabupaten Lumajang. Penelitian dan pengembangan ini menggunakan jenis penelitian teknik analisis data berupa analisis deskriptif kualitatif dan kuantitatif Hasil pengembangan multimedia interaktif memuat materi keragaman suku bangsa dan agama di Indonesia pada Tema 7 Indahnya keragaman di Negeriku untuk kelas IV sekolah dasar. Multimedia interaktif yang dikembangkan memperoleh persentase penilaian oleh ahli media yaitu 100 persen atau dikategorikan sebagai media sangat valid, persentase penilaian oleh ahli materi dengan rata-rata 89 persen atau dikategorikan media sangat valid.sedangkan kepraktisan media yang dikembangkan memperoleh persentase penilaian oleh guru sebesar 96 persen atau dikategorikan sebagai media yang sangat praktis dan persentase penilaian yang dilakukan oleh siswa berjumlah delapan belas siswa yakni 99,62 persen atau dikategorikan sebagai media yang sangat praktis. Media pembelajaran multimedia interaktif yang dikembangkan dikategorikan sebagai media yang sangat valid dan sangat praktis, serta media pembelajaran multimedia interaktif dapat diimplementasikan dalam proses pembelajaran selanjutnya. Peneliti selanjutnya dapat mengembangkan media dengan cangkupan yang lebih luas.